Effectiveness of Standard Treatment for Stage 4 Colorectal Cancer: Traditional Management with Surgery, Radiation, and Chemotherapy - Feria, Alejandro; Times, Melissa (Clinics in Colon and Rectal Surgery, 2023)
Colorectal cancer (CRC) is the second most common cause of cancer-related death in the United States comprising 7.9% of all new cancer diagnoses and 8.6% of all cancer deaths. The combined 5-year relative survival rate for all stages is 65.1% but in its most aggressive form, stage 4 CRC has a 5-year relative survival rate of just 15.1%. For most with stage 4 CRC, treatment is palliative not curative, with the goal to prolong overall survival and maintain an acceptable quality of life.The identification of unique cancer genomic and biologic markers allows patient-specific treatment options. Treatment of stage 4 CRC consists of systemic therapy with chemotherapeutic agents, surgical resection if feasible, potentially including resection of metastasis, palliative radiation in select settings, and targeted therapy toward growth factors. Despite advances in surgical and medical management, metastatic CRC remains a challenging clinical problem associated with poor prognosis and low overall survival.
Keywords: colorectal cancer treatment; stage 4 colon cancer